PKM Utilization of Natural Ingredients, Spices and Coconut as Family Drinks in an Effort to Increase Body Immune During Covid Conditions in Bungus Teluk Kabung District, Bungus Barat Village, Padang City - Suryelita Suryelita; Syamsi Aini; Desy Kurniawati; Indang Dewata; Sri Benti Etika; Melindra Mulia; Trisna Kumala Sari (Pelita Eksakta, 2022)
During the pandemic, people's activities are limited outside the home. However, this condition has an impact on their income economy. People can return to their activities to meet their needs by implementing a new normal life through health protocols. However, information and knowledge on how to maintain body immunity and the implementation of a new normal life are still limited. Therefore, it is necessary to disseminate information about the importance of body immunity during this pandemic. One of the areas affected by this pandemic is Bungus Barat Village, Bungus Teluk Kabung District. To answer the problems that arise in this area, it is necessary to carry out service activities that aim to provide information to the community, especially mothers who are the spearheads of families who are members of the association of PKK women in West Bungus Village on how to increase and maintain immunity during the pandemic. This increase in immunity includes lifestyle and diet that must be followed in the new normal life. Participants in this service activity include representatives of PKK women in West Bungus Village. The activity is in the form of implementation which is divided into two stages, namely guided activities, and independent activities. In the guided activities, interactive and practical counseling methods are used. Meanwhile, in independent activities, the target is to carry out the practice of making spice drinks and VCO in groups again. The results of the activity showed an increase in target knowledge about kitchen spices and coconut into VCO and nutritious spice drinks. The target community, namely PKK women, is also interested in consuming and producing their own VCO and spice drinks that have been made. In addition, from this activity, the community gained a good understanding of what to do during this pandemic, not only in complying with health protocols but also in regulating lifestyle and eating patterns.